An FPGA-based approach to the compacting of the Sunsat 1 TTM System - Le Roux, A. G.(Abraham Gerhardus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1998.